2021
DOI: 10.1186/s12888-021-03589-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with post-traumatic stress disorder in healthcare workers exposed to COVID-19 in Wuhan, China: a cross-sectional survey

Abstract: Background The COVID-19 pandemic has posed significant threats to both the physical and psychological health of healthcare workers working in the front-line combating COVID-19. However, studies regarding the medium to long term impact of COVID-19 on mental health among healthcare workers are limited. Therefore, we conducted this cross-sectional survey to investigate the prevalence, factors and impact of post-traumatic stress disorder (PTSD) in healthcare workers exposed to COVID-19 8 months aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 38 publications
7
28
0
Order By: Relevance
“…ICUs are the main battleground for treating patients with severe COVID-19. The critical nursing team has a precise and skilled professional level in the treatment and care of critically ill patients and can grasp the operation skills of various rescue and life support equipment proficiently ( 41 ). During the pandemic, nurses gained positive and negative psychological experiences but always prioritized the patient's treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ICUs are the main battleground for treating patients with severe COVID-19. The critical nursing team has a precise and skilled professional level in the treatment and care of critically ill patients and can grasp the operation skills of various rescue and life support equipment proficiently ( 41 ). During the pandemic, nurses gained positive and negative psychological experiences but always prioritized the patient's treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19 Similar to our findings on external support, previous studies also highlighted the importance of support from social mechanisms, positive public news, the positive atmosphere of a team, support from group leaders or team members, and support from family members. 28 A recent study claimed that psychological Open access resources in the media or positive news help them through the epidemic. 15 Correspondingly, support from supervisors and colleagues has been proven to be an effective way to overcome psychological burdens.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of scalar invariance of the refined version MBI over the pandemic waves has some consequences. Cross-sectional studies have shown that burnout after the pandemic has a very high prevalence, and longitudinal studies that burnout levels have increased as a result of the pandemic [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. If the lack of longitudinal scalar invariance that was found in this study is generalized to other countries and populations, it might be hard to disentangle the presence of true differences in the levels of burnout from differences in how HCWs respond to the items of the MBI from the pandemic on.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic seems to have exacerbated this issue due to repeated exposure to life-threatening situations, fear of contagion, shift overload and changes in work organization [ 8 , 9 ]. The results of longitudinal studies and the comparison between the estimates of the studies performed before and during the pandemic show a high prevalence and a marked increase of the levels of anxiety, with estimates from studies performed during the pandemic ranging from 22% to 31%, depression (from 17% to 36%), PTSD symptoms (from 13% to 37%) and burnout (from 36% to 52%) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among the protective factors, studies have shown that resilience and post-traumatic growth helped to buffer the impact of the pandemic, suggesting that these factors should be taken into account in order to describe the mental health of HCWs [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%